Perkawinan Adat “Rasan Jahat” Perspektif Maqashid Syariah (Studi Desa Sako Kecamatan Rambutan Kabupaten Banyuasin) - Mawardi, Muhammad Afiq Zamzami; Rochmiyatun, Siti; Azhari, Ari; Fani, Khairul (MU'ASYARAH: Jurnal Kajian Hukum Keluarga Islam, 2025)
: Marriage for Muslims is something that is very sacred and has a sacred purpose and cannot be separated from the provisions stipulated by Islamic law. The existence of customary marriage regulations between one indigenous community and another, with differences in these customary regulations, often resolves inter-customary marriages into protracted problems. Sako Village, Rambutan District, Banyuasin Regency has Sako Village Regulation Number 05 of 2014 concerning the Existence of Traditional Law Communities and the Compilation of Sako Village Customs. In one of the chapters discussing traditional marriages, the village regulations explain that there are 2 types of marriage feelings, one of which is "Evil Rasan". "Rasan Evil" Traditional Marriage is a form of marital deviation that occurs in Sako Village, Rambutan District, Banyuasin Regency. This research uses a qualitative approach method with the type of field research (Field Research). This study was carried out by interviewing informants in the field regarding the "Rasan Evil" traditional marriage mechanism from the Maqashid Syariah perspective and the primary data sources used were the results of interviews with informants in the field, and also secondary data sources such as books, journals, mass media, and related regulations regarding marriage. The research results show that the "Evil Rasan" Traditional Marriage is caused by 2 things, namely First, it is based on the "Pull" from the Maqasid Syariah perspective, in this case the aim is to protect offspring (hifdz an-nasl). Second, based on being pregnant out of wedlock, when viewed from the Maqashid Sharia perspective, this traditional marriage is not in accordance with the objectives of Sharia law.: Marriage for Muslims is something that is very sacred and has a sacred purpose and cannot be separated from the provisions stipulated by Islamic law. The existence of customary marriage regulations between one indigenous community and another, with differences in these customary regulations, often resolves inter-customary marriages into protracted problems. Sako Village, Rambutan District, Banyuasin Regency has Sako Village Regulation Number 05 of 2014 concerning the Existence of Traditional Law Communities and the Compilation of Sako Village Customs. In one of the chapters discussing traditional marriages, the village regulations explain that there are 2 types of marriage feelings, one of which is "Evil Rasan". "Rasan Evil" Traditional Marriage is a form of marital deviation that occurs in Sako Village, Rambutan District, Banyuasin Regency. This research uses a qualitative approach method with the type of field research (Field Research). This study was carried out by interviewing informants in the field regarding the "Rasan Evil" traditional marriage mechanism from the Maqashid Syariah perspective and the primary data sources used were the results of interviews with informants in the field, and also secondary data sources such as books, journals, mass media, and related regulations regarding marriage. The research results show that the "Evil Rasan" Traditional Marriage is caused by 2 things, namely First, it is based on the "Pull" from the Maqasid Syariah perspective, in this case the aim is to protect offspring (hifdz an-nasl). Second, based on being pregnant out of wedlock, when viewed from the Maqashid Sharia perspective, this traditional marriage is not in accordance with the objectives of Sharia law.